2017
DOI: 10.1080/10428194.2017.1330472
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors predicting the survival of pediatric patients with relapsed/refractory non-Hodgkin lymphoma who underwent hematopoietic stem cell transplantation: a retrospective study from the Turkish pediatric bone marrow transplantation registry

Abstract: We examined outcomes of 62 pediatric patients with relapsed or refractory non-Hodgkin lymphoma (rr-NHL) who underwent hematopoietic stem cell transplantation (HSCT). The overall survival (OS) and event-free survival (EFS) rates were 65% and 48%, respectively. Survival rates for patients with chemosensitive disease at the time of HSCT were significantly higher than those of patients with chemoresistant disease (69% vs. 37%, p = .019 for OS; 54% vs. 12%, p < .001 for EFS; respectively). A chemoresistant disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Hazar et al evaluated 21 patients with LBL (5 and 16 patients with B-LBL and T-LBL, respectively) undergoing HSCT. Among them, 16 patients received allo-HSCT, while 5 patients received auto-HSCT, and the overall OS and EFS were 48% and 44%, respectively (36). In a retrospective multicenter study of the largest series of LBL patients treated with auto-HSCT or MSD-HSCT, MSD-HSCT was associated with fewer relapses than was auto-HSCT (5-year rate, 34% vs. 56%; P=0.004) but was also associated with higher TRM (6-month rate, 18% vs. 3%; P=0.002), which obscured any potential survival benefit (22).…”
Section: Discussionmentioning
confidence: 99%
“…Hazar et al evaluated 21 patients with LBL (5 and 16 patients with B-LBL and T-LBL, respectively) undergoing HSCT. Among them, 16 patients received allo-HSCT, while 5 patients received auto-HSCT, and the overall OS and EFS were 48% and 44%, respectively (36). In a retrospective multicenter study of the largest series of LBL patients treated with auto-HSCT or MSD-HSCT, MSD-HSCT was associated with fewer relapses than was auto-HSCT (5-year rate, 34% vs. 56%; P=0.004) but was also associated with higher TRM (6-month rate, 18% vs. 3%; P=0.002), which obscured any potential survival benefit (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, Qi et al used the Cox proportional hazard to assess bleeding's independent prognostic value and fine-gray competing risk models for survival analyses, lasso regression to select a training set to derive the bleeding score, and logistic regression to derive the value-added score. There was an increased cumulative incidence of overall mortality (HR = 10:90), 11 Computational and Mathematical Methods in Medicine nonrelapse mortality (HR = 14:84), and combined endpoints (HR = 9:30), but not the cumulative incidence of relapse in higher bleeding class HSCT patients [58]. The performance comparison of our methodology with some of these stateof-the-art ones is provided in Table 6.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of data are limited to retrospective analyses. These studies are heterogeneous, including series of selected patients submitted to transplant (Loiseau et al , 1991; Bureo et al , 1995; Won et al , 2006; Giulino‐Roth et al , 2013), series of patients derived from transplant registries (Ladenstein et al , 1997; Gross et al , 2010; Hazar et al , 2018), or series of patients relapsed from multicentre protocols (Philip et al , 1993; Jourdain et al , 2015; Rigaud et al , 2019). The conditioning regimens are also heterogeneous.…”
Section: Haematopoietic Stem Cell Transplantmentioning
confidence: 99%
“…Multivariate analysis showed a higher risk of treatment failure for patients who were not transplanted in CR ( P < 0·01), regardless of the donor type. Hazar et al (2018) reported data from the Turkish paediatric bone marrow transplantation registry on 62 r/r NHL patients transplanted between 2006 and 2014. For the 22 B‐NHL, the OS rate was 68%; patients with chemoresistant disease at HSCT had a significantly lower OS rate than those with a chemosensitive disease (81% vs. 33%, P < 0·001).…”
Section: Haematopoietic Stem Cell Transplantmentioning
confidence: 99%